2008
DOI: 10.1111/j.1468-2389.2008.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Elaboration on Responding to Situational Judgment Test Items

Abstract: Although faking has been identified as a potential problem in situational judgment tests (SJTs), no studies have investigated proactive approaches for controlling faking in SJTs. Therefore, this study examined the impact of elaboration on responding to SJT items. Elaboration was operationalized as reason-giving. Two hundred and forty-seven master students were assigned to either an honest or a fake condition, and to a non-elaboration or an elaboration condition. Results showed that elaboration decreased the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
1
15
1
Order By: Relevance
“…Doing so provides estimates that underrepresent the reliability of the measure. When researchers find low internal consistency in their study, they fall back on stating that this is expected for heterogeneous content that is factorially complex and generally perform no further analysis (e.g., Lievens & Peeters, ; Peeters & Lievens, ).…”
Section: Introductionmentioning
confidence: 99%
“…Doing so provides estimates that underrepresent the reliability of the measure. When researchers find low internal consistency in their study, they fall back on stating that this is expected for heterogeneous content that is factorially complex and generally perform no further analysis (e.g., Lievens & Peeters, ; Peeters & Lievens, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several faking studies on SJTs attempted to reduce faking (Lievens & Peeters, 2008;Oostrom et al, 2017). The most common approach is asking individuals what they should do (i.e., knowledge instructions) as opposed to asking individuals what they would actually do (i.e., behavioral tendency instructions) (Nguyen et al, 2005).…”
Section: Faking On Sjtsmentioning
confidence: 99%
“…Unlike the extended research on faking on personality tests, the number of published studies on faking on SJTs is limited (Table ). As with personality tests, lab studies showed that individuals are able to obtain higher SJT scores if they are instructed to fake (Lievens & Peeters, ; Nguyen, Biderman, & McDaniel, ; Oostrom, Köbis, Ronay, & Cremers, ; Peeters & Lievens, ). The size of the faking effects seems to depend on the order in which the fake and honest conditions are presented to the respondent.…”
Section: Introductionmentioning
confidence: 99%
“…Response distortion or faking can attenuate the criterion‐related validity of tests (Peeters & Lievens, 2005), negatively affect construct validity (Stark, Chernyshenko, Chan, Lee, & Drasgow, 2001), and affect who is hired (Rosse et al., 1998). As such, scholars have sought to control job applicants’ tendencies to inflate their responses through both reactive and proactive approaches (Lievens & Peeters, 2008; Vasilopoulos, Cucina, & McElreath, 2005).…”
mentioning
confidence: 99%
“…To date, four empirical studies have been conducted to test the usefulness of this technique. Three of these studies investigated its impact on biodata responses (Ramsay, Schmitt, Oswald, Kim, & Gillespie, 2006; Schmitt & Kunce, 2002; Schmitt et al., 2003), and one study investigated its impact on situational judgment test responses (Lievens & Peeters, 2008). The reported results provide initial empirical support for the usefulness of RET and show that requiring elaboration for biodata items reduces test scores.…”
mentioning
confidence: 99%